2000
DOI: 10.1053/rmed.1999.0690
|View full text |Cite
|
Sign up to set email alerts
|

Emphysematous lesions and lung function in healthy smokers 60 years of age

Abstract: We aimed to study the occurrence of emphysematous lesions in symptom free smoking men of about 60 years of age and in a matching group of never-smoking men and the relationship between pulmonary changes at high resolution computed tomography (HRCT) and lung function tests. Our investigation included 57 smoking and 32 never-smoking healthy men from a randomized epidemiological study. HRCT was performed at full inspiration with a 1.5 mm slice thickness and a 3 cm inter-slice distance. Evaluation was made by two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 24 publications
5
35
0
1
Order By: Relevance
“…The ECLIPSE study showed that patients with increasing GOLD (Global Initiative of Chronic Obstructive Lung Disease) severity tend to have a greater amount of emphysema. 8 Emphysematous lesions are well described in symptomfree smokers with normal lung function 10 and help to identify nonobstructed male smokers in whom airway obstruction is likely to develop. 11 We carried out a single-center, prospective, 1-year study of the effects of smoking cessation in a group of asymptomatic smokers, selected on the basis of moderate to severe COPD on spirometry, and in a group with normal spirometry.…”
Section: Discussionmentioning
confidence: 99%
“…The ECLIPSE study showed that patients with increasing GOLD (Global Initiative of Chronic Obstructive Lung Disease) severity tend to have a greater amount of emphysema. 8 Emphysematous lesions are well described in symptomfree smokers with normal lung function 10 and help to identify nonobstructed male smokers in whom airway obstruction is likely to develop. 11 We carried out a single-center, prospective, 1-year study of the effects of smoking cessation in a group of asymptomatic smokers, selected on the basis of moderate to severe COPD on spirometry, and in a group with normal spirometry.…”
Section: Discussionmentioning
confidence: 99%
“…HRCT imaging detects early emphysema by identifying pulmonary tissue with radiologic attenuation below a predetermined threshold, findings that roughly correlate with a low DL CO and pathologic evidence of emphysema (74)(75)(76)(77)(78)(79)(80). Although several studies have shown that a significant proportion of asymptomatic smokers have HRCT evidence of emphysema (78,(81)(82)(83), early HRCT findings of ''emphysema'' are not proven to be correlated directly with lung destruction (84)(85)(86)(87)(88)(89)(90). Hyperpolarized gas diffusion-weighted magnetic resonance imaging has also been used to identify emphysema, with a correlation of elevated levels of the apparent diffusion coefficient with decreased DL CO (91).…”
Section: Early Detection Of Lung Destructionmentioning
confidence: 99%
“…We did not include a group of never-smokers since previous studies have shown that non-smokers generally do not develop emphysema [8,10,15]. In the studies by Tylen et al and Vikgren et al [10,15], which included considerably older subjects, 60Á67 years old, emphysema was diagnosed in only one of 32 (3%) never-smokers and none of 26 never-smokers, respectively. It could be criticized that only one experienced thoracic radiologist evaluated the HRCT.…”
Section: Limitations and Strengthmentioning
confidence: 99%
“…High resolution computed tomography (HRCT) may detect parenchymal lung abnormalities in healthy, symptom-free smokers [8]. HRCT is a sensitive method for detection of emphysema and studies suggest that HRCT could be used as a method for early detection of COPD [9,10].…”
mentioning
confidence: 99%